KECEMASAN DAN KESEDIHAN IBU DALAM MERAWAT ANAK USIA PRASEKOLAH YANG TERDIAGNOSA LEUKEMIA LIMFOBLASTIK AKUT DI RSUP SANGLAH DENPASAR: KECEMASAN DAN KESEDIHAN IBU DALAM MERAWAT ANAK USIA PRASEKOLAH YANG TERDIAGNOSA LEUKEMIA LIMFOBLASTIK AKUT DI RSUP SANGLAH DENPASAR - Gede Budi Widiarta; Made Martini (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2018)
Cancer remains the second leading cause of death in children aged 5 to 14 years (Ward, et all, 2014). It is estimated that the incidence of all cancers in children approximately 80% are acute lymphoblastic leukemia, the peak incidence of this leukemia occurred in toddler and preschool children between the ages of 2 to 6 years (James and Ashwill, 2007). The purpose of this study was to explore the mother’s experience of caring for preschool children with acute lymphoblastic leukemia. This study used a qualitative descriptive phenomenology, six participants was interviewed in depth. Data was analyzed using Collaizzi method of analysis. This study resulted themes: distressing and anxiety because of the uncertainty of the future of children; Caring for a children with cancer should not be interrupted only at hospitals, required the participation of the family, especially mother as a caregiver for the child at home. Nurses are expected to always provide information on developments in result treatment update in families with child cancer.